Réponses

Meilleure réponse !
2013-09-20T20:00:55+02:00
A = 3(x-10)(x+10)+(2x+5)(x+10)
= 3  * x + 3 * (-10) + 3 * x + 3 * 10 + 2x * x + 2x * 10 + 5 * x + 5 * 10
= 3x + (-30) + 3x + 30 + 
 2x^{2} + 20x + 5x + 50
= 31x + 50 +  2x^{2}

B = 4(3x+6)(5x+1)-2(3x-6)^2
= 4 * 3x + 4 * 6 + 4 * 5x + 4 * 1 -2 * 3x + (-2) * (-6) ^2
= 12x + 24 + 20x + 4 - 6x + 12 ^2
= 38x + 40 ^2
2013-09-20T20:04:52+02:00
A : 3(x-10)(x+10)+(2x+5)(x+10) = (x+10)  [ (3x-30)+(2x+5)] = (x+10) ( 5x-25)
=5 (x+10) (x-5) = 5xcarré + 25x -250

B : 4(3x+6)(5x+1)-2(3x-6)^2 = 4( 15x^2+33x+6) -2 ( 9x^2-36x+36)
=60 x^2 +133x +24-18x^2+72x-72= 42 x^2 +205x - 48